Ecuador : An Economic and Social Agenda in the New Millennium - .Giugale, Marcelo M.; López-Cálix, José Roberto (the international bank for reconstruction and development, 2003)
The book focuses on three overarching themes: fiscal consolidation and growth; social development; and, quality of government, and, documents Ecuador's development trends, policies, and options. The fundamental challenges facing the country are identified within this book, and the solutions represent a break with the past: this is a proposal for an agenda with a broad, and integrated vision of economic, and social development in Ecuador.